2020
DOI: 10.1002/sdtp.13872
|View full text |Cite
|
Sign up to set email alerts
|

23‐4: Full Color, Active‐Matrix Micro‐LED Display with Dual Gate a‐IGZO TFT Backplane

Abstract: A full color, active matrix micro‐LED (AMLED) display using dual‐gate (DG) a‐IGZO TFT and lateral micro‐LED chip is demonstrated. It is found that DG a‐IGZO TFT backplane is suitable for driving large area, full color micro‐LED display. In this research, the driving TFTs for red, green and blue µ‐LEDs exhibit a uniform threshold voltage (Vth) and linear mobility characteristics as 0.4, 0.3 and 0.3 V, and 7.79, 7.83 and 7.78 cm2/Vs, respectively. Also, the full color AMLED display has a 58 ppi with diagonal 2‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Therefore, it is very necessary to develop LED display screens with glass substrates, which can realize LED displays with smaller pitches, and is expected to greatly reduce costs of production. It is found that the IGZO TFT backplane is very suitable to be used in largesize LED displays [5,6]. However, since the IR drop effect will cause in-plane differences of luminance, the chip size of the LED display should not be too large.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very necessary to develop LED display screens with glass substrates, which can realize LED displays with smaller pitches, and is expected to greatly reduce costs of production. It is found that the IGZO TFT backplane is very suitable to be used in largesize LED displays [5,6]. However, since the IR drop effect will cause in-plane differences of luminance, the chip size of the LED display should not be too large.…”
Section: Introductionmentioning
confidence: 99%